Exploring the root causes of the rise of the Islamic State West African Province (ISWAP) in sub-Saharan Africa, specifically Nigeria: A regional security constellation perspective - Edward Plockey (Journal of Global Faultlines)
Insurgency has infiltrated contemporary Nigerian culture, whether it involves abduction by the Niger Delta militants in the south, banditry and cattle rustling in the northwest, north central or southwest regions, or bombings by the Islamic State West African Province (ISWAP) in the northeast and north central regions. The Nigerian populace and its neighbors at the Lake Chad periphery continue to suffer significantly from these acts of terrorism. The point made in this paper is that the insecurity burdening contemporary Nigeria, as a result of ISWAP’s activities, mainly in the northeast, is due to the long-term failure of the Nigerian state to address the domestic issues – such as resource distribution, ethnic tensions, corruption, and economic inequalities, to name a few – that underpin some of these security threats. The Nigerian state has also been unable to demonstrate characteristics or achieve goals that are considered natural or advantageous to the entire population. The paper examines the conditions leading to the rise of the jihadist group ISWAP by using the concepts of regional security constellation theory as advanced by Buzan & Weaver (2003) .